Cardiac Infarction Injury Score predicts cardiovascular mortality in apparently healthy men and women. Issue 1 (July 1994) - Dekker, J M; Schouten, E G; Pool, J; Kok, F J
Abstract : OBJECTIVE–The Cardiac Infarction Injury Score (CIIS) is an electrocardiogram classification system that was developed to identify ischaemic heart disease. As well as being of diagnostic value, the CIIS may also be of prognostic value. DESIGN–The prognostic value of the CIIS for mortality of coronary heart disease and cardiovascular disease was assessed in a 28 year follow up study of 3091 apparently healthy middle aged men and women (Dutch Civil Servants Study). RESULTS–The rates of coronary heart disease and cardiovascular disease mortality during the first 15 years of follow up were significantly higher in men and women with a CIIS of > 10 than in those with a CIIS of < or = 0 (rate ratio of coronary heart disease mortality 2.9 (95% confidence interval 1.5 to 5.8) for men and 5.6 (2.0 to 15.5) for women). Coronary heart disease mortality was also higher in men with a CIIS of 1-10 than in men with CIIS of < or = 0. When individuals with major Minnesota code items were excluded, the associations were weaker and no longer statistically significant. CONCLUSION–These results indicate that a high CIIS is a risk indicator for coronary heart disease mortality in the general population. Classification of electrocardiograms by means of the CIIS seems to be equivalent to classification by a combination of Minnesota code items. Because CIIS coding is simpler and can be performed by computer it may be more efficient than the Minnesota code for classifying cardiac injury in epidemiological studies.